Analisis Faktor-faktor yang Mempengaruhi Perilaku Konsumen dalam Pengambilan Keputusan Pembelian White Coffe - Khasan, Umar (Cakrawala, 2018)
The Goals of this research are analyze factors affect to purchase products White Coffee. Research was carried out in Hypermart Bangkalan. Sample was taken by Â accidentl sampling method. Data were analyzed by qualitative diskriptif. The result of factors affect the purchase decision of White Coffee are culture.